2002
DOI: 10.1002/jgm.355
|View full text |Cite
|
Sign up to set email alerts
|

Multiple muscles in the AMD quail can be “cross‐corrected” of pathologic glycogen accumulation after intravenous injection of an [E1‐, polymerase‐] adenovirus vector encoding human acid‐α‐glucosidase

Abstract: Adenovirus-mediated transduction of the hGAA gene, followed by hepatic secretion, uptake, and cross-correction of the pathologic glycogen accumulation noted in multiple muscles of both the AMD mouse and AMD quail, adds support to the notion that gene transfer strategies (Ad-mediated or other agents) targeting liver tissues with the hGAA gene are likely to be highly efficacious in humans affected by AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…Once in the lysosome, the precursor is cleaved to its active form, resulting in the correction of glycogen storage in multiple affected muscle tissues, this effect was sustained for up to 6 months in the longest experiments. [9][10][11] This result has been achieved in two animal models of GSD-II, the GAA-KO mouse and the AMD quail, 10,14 suggesting that similar levels of efficacy may be achievable in humans as well. However, we have also noted that anti-hGAA antibodies were rapidly elicited (although the absolute amounts could be reduced by use of liver-specific promoter elements 11 ) in the GAA-KO mouse model of Pompe disease (the GAA-KO mouse does neither express any murine GAA RNA nor protein 16 ) after Admediated transfer of the hGAA gene.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Once in the lysosome, the precursor is cleaved to its active form, resulting in the correction of glycogen storage in multiple affected muscle tissues, this effect was sustained for up to 6 months in the longest experiments. [9][10][11] This result has been achieved in two animal models of GSD-II, the GAA-KO mouse and the AMD quail, 10,14 suggesting that similar levels of efficacy may be achievable in humans as well. However, we have also noted that anti-hGAA antibodies were rapidly elicited (although the absolute amounts could be reduced by use of liver-specific promoter elements 11 ) in the GAA-KO mouse model of Pompe disease (the GAA-KO mouse does neither express any murine GAA RNA nor protein 16 ) after Admediated transfer of the hGAA gene.…”
Section: Discussionmentioning
confidence: 76%
“…Our results have been confirmed in GAA-KO mice and AMD quails, both relevant animal models of GSD-II. [12][13][14] More importantly, high-level hepatic secretion of hGAA results in a near complete clearance of glycogen in cardiac and skeletal muscles within 12 days of the vector injection. [9][10][11] In addition, transgenic GAA-KO mice overexpressing GAA in their liver tissues also demonstrated widespread glycogen clearance, relative to attempts to secrete hGAA transgenically from skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our group as well as others have tested several gene therapy approaches for GSD-II [13,[20][21][22]. The most clinically promising of these includes intravenous injection of an [E1-, polymerase-] AdhGAA vector, which demonstrated efficacy in several GSD-II animal models (both AMD quails and GAA-KO mice) [10,12]. By this approach hepatically secreted hGAA is taken up by skeletal and cardiac muscle cells via receptor-mediated endocytosis, with systemic reduction of glycogen storage being rapidly, and persistently, achieved.…”
Section: Discussionmentioning
confidence: 98%
“…These results closely approximated results previously achieved in murine and quail models of GSD-II. 6,11 Results Sustained high level baboon GAA (bGAA) production and plasma distribution of bGAA in mice by HD-Ad.…”
mentioning
confidence: 99%
“…2,5 We previously demonstrated in mouse and quail models of Pompe disease that if enough GAA enzyme is expressed in the liver using liver-targeted gene therapy (adenovirus or adeno-associated virus (AAV)), the liver can secrete large amounts of the 110-kDa precursor form of GAA, thereby allowing GAA to be systemically taken up by multiple tissues, and allow for disease stabilization and/or reversal. [6][7][8][9][10][11][12][13][14][15][16] More recently, in GSD-II mice, we demonstrated that using a helper-dependent adenovirus (HD-Ad) expressing human GAA (HD-Ad/hGAA) produced high plasma levels of GAA and reversed the muscular pathology throughout the animal for over 300 days. 6 Despite these and other successes of liver-directed gene therapy in mice, 7,[17][18][19][20] translating these approaches into non-human primates (NHPs) has proven difficult.…”
mentioning
confidence: 99%